Análise da presença da inversão da razão CD4:CD8 em idosos e seu perfil celular e bioquímico - Müller, Guilherme Cerutti (2015)
Aging has been associated with increased generation of free radicals as well as immunosenescence. Previous studies have identified older individuals with inverted T CD4:CD8 cell ratio and increased immunity to cytomegalovirus (CMV). Here, we investigated markers of oxidative stress and antioxidant defences in older individuals with inverted CD4:CD8 T-cell ratio. From 421 healthy community-dwelling older adults recruited, 61 subjects were identified with inverted CD4:CD8 T-cell ratio. Older individuals with a CD4:CD8 ratio < 1 had increased levels of plasma advanced oxidation protein products (AOPP) and Ferric Reducing Ability of Plasma (FRAP), but reduced levels of thiobarbituric acid reactive substances (TBARS) as compared to subjects with normal CD4:CD8 T-cell ratio. The CMV IgG serology was negatively correlated with CD4:CD8 ratio. These markers were more evident among elderly men than women. Our data suggest a close relationship between chronic CMV infection and oxidative profile in older individuals in the midst of its influence on the peripheral T-cell subsets.